KREATIVITAS EKONOMI MASYARAKAT LOKAL DI KERESIDENAN JEPARA 1830-1900 - Alamsyah, Alamsyah (Paramita: Historical Studies Journal, 2013)
The research shows that in the period of 1830-1900 the inhabitants of Jepara Residency were quite dynamic even though the economic principle had moved from maritime to agrarian. The inhabitantsÃ¢â¬â¢ creativity which was based on soft skill raised the economic autonomy. They did not rely on the maritime and plantation economy so much. However, the plantation economy gave an opportunity for the creative economy to be born. Then, the inhabitantsÃ¢â¬â¢ economic creativity created industry and indigenous handicraft. The introduction of export plants which was supported by capitalism did not raise the inhabitantsÃ¢â¬â¢ dependence towards the colonial economic system. What happened precisely was the interdependence between government, capitalist and inhabitants. When the colonial economic penetration was more intensive, the people were able to adapt to the economic change without being dependent upon the colonial economic structure. It was shown by the inhabitantsÃ¢â¬â¢ alternative economy. Key words: economic creativity, local society, Jepara residency ÃÂ Penelitian menunjukkan bahwa pada periode 1830-1900 penduduk Keresidenan Jepara cukup dinamis meskipun prinsip ekonomi telah berpindah dari maritim ke agraris. Kreativitas penduduk yang didasarkan pada soft skill mengangkat otonomi ekonomi. Mereka tidak begitu banyak bergantung pada ekonomi maritim dan ekonomi perkebunan. Namun, ekonomi perkebunan memberikan kesempatan bagi ekonomi kreatif untuk berkembang. Kemudian, kreativitas ekonomi penduduk menciptakan industri dan kerajinan asli. Pengenalan tanaman ekspor yang didukung oleh kapitalisme tidak meningkatkan ketergantungan penduduk terhadap sistem ekonomi kolonial. Apa yang terjadi justru adalah saling bergantungnya antara pemerintah, kapitalis dan penduduk. Ketika penetrasi ekonomi kolonial lebih intensif, orang-orang mampu beradaptasi dengan perubahan ekonomi tanpa bergantung kepada struktur ekonomi kolonial. Hal ini ditunjukkan dengan adanya ekonomi alternatif penduduk. Kata kunci: kreativitas ekonomi, masyarakat lokal, karesidenan Jepara